Pengaruh Pelatihan dan Pengembangan Sumber Daya Manusia terhadap Peningkatan Kinerja Karyawan dengan Motivasi Kerja sebagai Variabel Intervening (Studi Pada PT. Bank Jatim Tbk. Cabang Tulungagung) - Rina Dwi Oktarini; Budi Rahayu; Yogi Yunanto (Politeknik Raflesia Press, 2026)
This study was conducted to investigate the influence of training and human resource development on employee performance, with work motivation serving as an intervening variable at PT. Bank Jatim Tbk., Tulungagung Branch. Employing a quantitative research approach, the study relied on numerical data analyzed through statistical methods, ensuring adherence to scientific principles of concreteness, objectivity, measurability, rationality, and systematicity. The research population consisted of 200 employees, from which a sample of 67 respondents was selected. Data were collected using questionnaires, observation, interviews, and documentation, and subsequently analyzed through descriptive statistics and Partial Least Square (PLS).The findings reveal that training exerts a significant positive effect on employee performance, while human resource development also contributes positively and significantly to performance improvement. Furthermore, training was found to have a significant positive influence on employee motivation, and human resource development similarly enhanced motivation. Motivation itself was shown to play a crucial role in improving employee performance. Importantly, the study highlights that both training and human resource development positively affect performance when mediated by motivation, underscoring the central role of motivation as a bridge between organizational development initiatives and employee outcomes.In conclusion, the research demonstrates that systematic training and human resource development not only directly improve employee performance but also foster motivation, which in turn amplifies performance outcomes. These findings emphasize the importance of integrating motivational factors into organizational strategies for workforce development.